Mangampo: A Traditional Method from West Sumatra to Extract Gambir from Uncaria gambir - Anggraini, Tuty; Neswati; Asben, Alfi (Pakistan Journal of Nutrition, 2019)
Background and Objectives: This study is the first to explain in detail the process to extract gambir from Uncaria gambir. The aim of this study was to identify the process used to produce gambir. The process is called ‘mangampo,’ which yields dried gambir extracts. This unique traditional process can be useful for researchers to understand the conventional processing of natural resources with beneficial compounds. Materials and Methods: The materials used in this research were the leaves and branches of Uncaria gambir. This study conducted a survey of gambir processing methods in Pesisir Selatan and Lima Puluh Kota, the central regions of gambir production in West Sumatra. Results: The results of this study showed that the procedure of ‘mangampo’ consists of harvesting the leaves and branches, steaming until condensed water appears on the leaves and branches, pressing the steamed leaves and branches, collecting the extract, thickening the extract (until a paste forms), forming the gambir paste and drying the paste. Conclusion: In both regions (Pesisir Selatan and Lima Puluh Kota), the same principle of extracting gambir is used and ‘mangampo’ is a unique traditional method to produce gambir.